2008
DOI: 10.1159/000139772
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin: A Natural Biodegradable Scaffold in Vascular Tissue Engineering

Abstract: Arterial occlusive disease remains a major health issue in the developed world and a rapidly growing problem in the developing world. Although a growing number of patients are now being effectively treated with minimally invasive techniques, there remains a tremendous pressure on the vascular community to develop a synthetic small-diameter vascular graft with improved long-term patency rates. The field of tissue engineering offers an exciting alternative in the search for living organ replacement structures. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
113
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(114 citation statements)
references
References 203 publications
0
113
0
1
Order By: Relevance
“…Western blot analysis of MT1-MMP indicated that its activity after 4 h post-seeding was enhanced in both PEGylated and non-modified 3-D gels as compared to 2-D culture ( Figure 3B). MT1-MMP activity in 3-D PEGylated fibrin gels was markedly increased starting from day 6 (bands 8,9,11,12) and was comparable to the activity in non-modified fibrin.…”
Section: Huvecs and Hascs Express Various Mmps And Mt-mmps When Cultumentioning
confidence: 72%
See 1 more Smart Citation
“…Western blot analysis of MT1-MMP indicated that its activity after 4 h post-seeding was enhanced in both PEGylated and non-modified 3-D gels as compared to 2-D culture ( Figure 3B). MT1-MMP activity in 3-D PEGylated fibrin gels was markedly increased starting from day 6 (bands 8,9,11,12) and was comparable to the activity in non-modified fibrin.…”
Section: Huvecs and Hascs Express Various Mmps And Mt-mmps When Cultumentioning
confidence: 72%
“…Fibrin has been qualified as an appropriate natural protein matrix material for vascular tissue engineering due to its unique properties [9]. Fibrinogen, which is the fibrin precursor, is a blood protein and can be autologously derived.…”
Section: Introductionmentioning
confidence: 99%
“…The use of fibrin as a biomaterial results from its biocompatibility, biodegradability, injectability, and ability to enhance cell proliferation [334]. Currently, fibrin is investigated for use as drug delivery device [335] and cell carrier [336] and fibrin glues are commercially available (Evicel ® , Ethicon).…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 99%
“…Several methodologies for constructing blood vessel replacements with biological functionality have emerged. The most common strategies include the use of cell-seeded gels, cell self-assembly, cell-seeded biodegradable synthetic scaffolds and xenogeneic acellular materials [5].…”
mentioning
confidence: 99%
“…Fibrin gel offers a number of advantages over cell self-assembly [5,11]. Fibrin has many inherent characteristics making it an ideal material for endothelial and smooth muscle cell adherence and it produces autologous extra cellular matrix.…”
mentioning
confidence: 99%